Congenital cytomegalovirus related intestinal malrotation: a case report. Issue 1 (December 2016) - Colomba, Claudia; Giuffrè, Mario; La Placa, Simona; Cascio, Antonio; Trizzino, Marcello; De Grazia, Simona; Corsello, Giovanni
Abstract Background Cytomegalovirus is the most common cause of congenital infection in the developed countries. Gastrointestinal involvement has been extensively described in both adult and paediatric immunocompromised patients but it is infrequent in congenital or perinatal CMV infection. Case presentation We report on a case of coexistent congenital Cytomegalovirus infection with intestinal malrotation and positive intestinal Cytomegalovirus biopsy. At birth the neonate showed clinical and radiological evidence of intestinal obstruction. Meconium passed only after evacuative nursing procedures; stooling pattern was irregular; gastric residuals were bile-stained. Laparatomy revealed a complete intestinal malrotation and contextually gastrointestinal biopsy samples of the appendix confirmed the diagnosis of CMV gastrointestinal disease. Intravenous ganciclovir was initiated for 2 weeks, followed by oral valgancyclovir for 6 month. Conclusion CMV-induced proinflammatory process may be responsible of the interruption of the normal development of the gut or could in turn lead to a disruption in the normal development of the gut potentiating the mechanism causing malrotation. We suggest the hypothesis that an inflammatory process induced by CMV congenital infection may be responsible, in the early gestation, of the intestinal end-organ disease, as the intestinal malrotation. CMV infection should always be excluded in full-term infants presenting with colonic stricture or malrotation.